Competitive Strategies for Micro Small and Medium Enterprises during the Covid-19 Pandemic in Indonesia, Literature Review - Muhammad Taufiq Hidayat (Budapest International Research and Critics University, 2022)
This paper aims to find out the strategies used by Micro, Small and Medium Enterprises (MSMEs) in the Pandemic Period in Indonesia in order to be able to survive and compete. The research method used in this paper uses a literature review method from various articles discussing competitive strategies in the era of the Covid 19 Pandemic in Indonesia published in reputable online journals. The results of research based on journals that were observed as many as 20 national journals focused on the Competitive Strategy of MSMEs in the era of the COVID-19 pandemic, so there are several strategies used by MSMEs to be able to compete and survive are as follows: 1. Competitive strategywith pricing, product development, promotion, and product distribution (Porter 1998). As for the strategy to survive at an affordable price, StraStability/Growth strategy, Marketing Strategy (Communication, STP (Segmenting, Targeting and Positioning) and Scorpio/7P Model), Islamic-based MSME Strategy (with Islamic business ethics amanah, fatonah, tabligh and shidig) using SWOT analysis, Creative innovation in products, services and promotions andMSMEs need to pay attention to the Business Environment because it affects theOperating Strategy and Firm PerformanceThis study has the limitation of only providing an overview of the research results from the selected articles, but does not provide an analysis related to the selected articles.